Respostas cinéticas da frequência cardíaca na fase de recuperação de exercício submáximo em pacientes com Doença Pulmonar Obstrutiva Crônica e o impacto da sobreposição da Apneia Obstrutiva do Sono na capacidade funcional e modulação autonômica cardíaca em seguimento de um ano - Camargo, Patrícia Faria (2021)
Chronic Obstructive Pulmonary Disease (COPD) is characterized by chronic airflow obstruction, which is not fully reversible, in which some patients are exposed to episodes of hypoventilation, hypoxemia and respiratory disorders during sleep. Most COPD patients suffer from systemic manifestations, such as changes in the musculoskeletal and cardiovascular systems, with consequent hypoxemia, hypercapnia, parasympathetic airway hyperactivity, peripheral sympathetic activation and decreased baroreflex sensitivity. The association of COPD with other diseases, such as Obstructive Sleep Apnea Syndrome (OSA), can lead to the magnification of systemic manifestations with consequent impairments in exercise capacity, increased symptoms, readmissions and exacerbations of the disease. Study I, entitled “Association between predictors of functional capacity and heart rate off kinetics in patients with Chronic Obstructive Pulmonary Disease”, aimed to verify whether there is a relationship between functional capacity by the six-minute walk test (6MWT), kinetic behavior off of heart rate (HR) with direct and indirect functional assessment measures, such as handgrip strength (FPP) and the scores from the Duke Activity Status Index (DASI) and COPD Assessment Test (CAT) questionnaires. We found associations between direct and indirect predictors of functional capacity, symptoms and kinetic responses of HR. We conclude that performance in the 6MWT is directly associated with other powerful functional predictors as well as, inversely, with the kinetics off of HR in individuals with COPD. Such results suggest that the application of simpler tools in clinical practice can be useful in the evaluation of these patients. Then, study II, “Impact of Obstructive Sleep Apnea on cardiac autonomic control during the maneuver of respiratory sinus arrhythmia in patients with Chronic Obstructive Pulmonary Disease”, aimed to verify whether the concomitant presence of Obstructive Sleep Apnea Syndrome (OSA) in patients with COPD would impair cardiac autonomic modulation, with the participation of 20 patients (COPD, n=11; OSA-COPD, n=9). Patients underwent cardiac autonomic modulation under the condition of resting spontaneous breathing (SB) and controlled breathing, induced by the respiratory sinus arrhythmia (RSA-M) maneuver. Both groups showed impaired responses when SB and RSA-M were compared, with increased sympathetic modulation (LF) and sympathetic-vagal balance [LF/HF (p≤0.05)] and decreased parasympathetic modulation [HF (p≤0.05)] –– a pattern opposite to that expected for RSA-M. However, the complexity indices (Apen, Sampen, SD2) and in the time domain increased only for OSA-COPD, showing the most important worst in the total variability during RSA-M (p≤0.05). The results show that the presence of the overlap of these diseases leads to a negative impact on the autonomic control of HR and deep breathing exercises. The third study deals with the assessment of the impact of OSA on functional capacity and cardiac autonomic modulation in patients with COPD and aimed to assess this impact during a year of follow-up. Still, as a secondary objective, the study proposed to verify the probability that patients with OSA-COPD have a greater number of episodes of exacerbation and hospitalization. Thirty-four patients (COPD, n=17; OSA-COPD, n=17) underwent pulmonary function tests, echocardiography and polysomnography for diagnostic confirmation, disease staging, exclusion of any cardiac changes and allocation between groups. Then, they were submitted to the six-minute walk test (6MWT) to assess functional capacity and heart rate variability (HRV) during exercise. Subsequently, patients were followed up for twelve months to record outcomes such as exacerbation, hospitalization and deaths. After this period, patients were reassessed to verify the study's hypotheses. Both groups showed a decline in functional performance over the course of a year. However, the OSA-COPD group showed a greater decline when compared to the COPD group (p=0.003). Consequently, this same group also presented worse cardiac autonomic responses during the 6MWT with greater parasympathetic activation (p=0.03) and less complexity of the autonomic nervous system, in addition to being more likely to exacerbate (p=0.03), also in response to the one-year follow-up. Thus, we conclude that OSA in association with COPD produces deleterious effects on functional performance over the course of a year of follow-up, as well as a greater autonomic imbalance that negatively impacts clinical outcomes.